Prevalence and related factors of maternal severe complications "Maternal Near Miss" in Ahvaz, 2016 - Seyedeh Narges Hashemi; Poorandokht Afshari; Mojgan Javadnoori; Amal Saki Malehi (Mashhad University of Medical Sciences, 2020)
Introduction: Today, for better assessment of midwifery care quality, in addition to maternal death, a useful supplementary indicator, called "maternal near miss" (MNM) is used. It means that mothers who have survived due to complications of pregnancy or childbirth. Limited studies have been conducted in this regard in Iran and no study has been performed in Khuzestan to evaluate this index. This study was performed with aim to determine the prevalence and factors related to MNM in Ahwaz hospitals in 2016. Methods: This cross-sectional study was performed on 3002 delivery in 5 state hospitals in Ahwaz, from 22 May until 25 July 2016. WHO criteria was used for MNM including potential life-threatening conditions (cardiovascular, respiratory, renal, blood, coagulation, hepatic, and neurological disorders) and criteria for severe maternal complications (severe postpartum haemorrhage, severe pre-eclampsia, eclampsia, sepsis/severe systemic infection, and uterus rupture). The prevalence of MNM and related factors were investigated. Data were analyzed by SPSS software (version 22) and Chi-square, Mann-Whitney test, t-test and logistic regression. P<0.05 was considered statistically significant. Results: The prevalence of MNM was 29.6 per 1,000 live births. The most common direct causes of MNM cases were preeclampsia (49.5%) and severe postpartum hemorrhage (38.2%). 26 of MNM (29.2%) were admitted in intensive care units. The lower gestational age (p <0.001), lower education level (p <0.008), and cesarean delivery (p <0.001) were more likely to resulted in cases of MNM. Conclusion: As for the reasons of maternal death, preeclampsia and obstetrical hemorrhage were the main reasons for MNM. Cesarean and lower gestational age increase the likelihood of MNM.